Savings for unemployment in good or bad times: options for developing countries - David A. Robalino; Milan Vodopivec; András Bodor (Institute for the Study of Labor (IZA), 2009)
The paper describes and evaluates unemployment insurance savings accounts (UISAs) - a relatively new and not well-known way of providing unemployment benefits. The UISAs reduce work disincentives by allowing recipients to keep their own unused unemployment contributions, and offer the possibility to extend coverage to informal sector workers. In addition, if integrated with mandatory pension systems (and even social pensions), UISAs can be rapidly deployed and at a low cost, thus becoming a realistic tool to protect workers from the effects of the financial crisis. Even during normal times, the integration with the pension system - and social security in general - would give more flexibility to individuals in the management of short and long term savings (i.e., pension wealth) while avoiding unnecessary administrative costs. The paper discusses issues related to incentives, redistribution, and viability, and outlines a policy framework for design and implementation. It argues that the UISAs system is especially attractive for developing countries, where the self-policing nature of the system is particularly important given a much larger informal sector and weaker administrative capacity in comparison to developed countries.
urn:nbn:de:101:1-20091105873
Keywords: J65; J68; 330; Unemployment insurance; unemployment insurance savings accounts; unemployment; Arbeitslosenversicherung; Private Arbeitslosenversicherung; Sparen; Gesetzliche Rentenversicherung; Arbeitslosigkeit; Informeller Sektor; Konjunktur; Entwicklungsländer